Relating costs to the user value of farmland biodiversity measurements. (1st January 2016) - Targetti, S.; Herzog, F.; Geijzendorffer, I.R.; Pointereau, P.; Viaggi, D.
Abstract: The impact of agricultural management on global biodiversity highlights the need for farm-scale monitoring programmes capable of determining the performance of agriculture practices. Yet the identification of appropriate indicators is a challenging process and one that involves considering a number of different aspects and requirements. Besides the attention given to scientific effectiveness, relevant but less studied issues related to biodiversity measurements include the economic feasibility of monitoring programmes and the relevance of indicators for different end-users. In this paper, we combine an analytic assessment of costs and a stakeholder-based evaluation of the usefulness of a set of biodiversity-related parameters (habitat mapping, vegetation, bees, earthworms, spiders, and a farmer questionnaire) tested for scientific consistency in 12 European case studies and on more than 14, 000 ha of farmland. The results point to the possibility of meeting the expectations of different end-users (administrators, farmers and consumers) with a common indicator set. Combining costs and usefulness also suggests the possibility of designing more efficient monitoring approaches involving private agencies and networks of volunteers and farmers for the field data collection at different stages of a monitoring programme. Although complex, such an approach would make it possible to enhance the effectiveness of available funds for farmland biodiversity monitoring. Highlights: The work focuses on the usefulness and costs of farmland biodiversity indicators. Farm-scale biodiversity parameters tested in a Europe-wide trial were evaluated. A combination of cost estimations and stakeholder assessments is proposed. The possibility of meeting the expectations of different end-users was confirmed. The involvement of different actors may enhance the cost-efficiency of monitoring.